Measuring The Maturity Of Guyana’s Construction Industry Using The Construction Industry Macro Maturity Model (CIM3) - Willis, Christopher J.; Rankin, Jeff H. (Penerbit Universiti Sains Malaysia, 2010)
The newly developed Construction Industry Macro Maturity Model (CIM3) was used to measure the maturity of Guyana‘s construction industry. The CIM3‘s assessment provides a leading indication of performance by relating the maturity of a set of management and operation key practices in the construction industry to the achievement of various performance objectives that lead to the realisation of the construction industry‘s performance goals. The implementation of the CIM3 in Guyana relied upon the use of an expert group of construction industry professionals who were elicited to provide the input information for the model. It was found that Guyana‘s construction industry is least mature with respect to health and safety management and most mature with respect to cost management. Overall, Guyana‘s construction industry is immature, and a translation of its maturity to represent the level of realisation of its combined performance goals indicates that its lagging or after-the-fact performance indicators are likely to be poor.